2021
DOI: 10.3390/catal11030345
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Combination Mechanism for Catalysts: A Game-Theoretical Approach

Abstract: Catalysts, artificially or naturally generated, are often considered to be important factors in numerous chemical processes. Although each catalyst can act under its own characteristics, the efficiency of chemical interactions can be enhanced by a balanced combination of different catalysts. On the other hand, many game-theoretical results have been widely applied to seek the optimal or balanced state for efficiency regulation, resource control, portfolio allocation, and behavior simulation in modern academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the past, combinations were always estimated by empirical rule judgments, literature comparison simulations, circular errata corrections and so on. Although the MLII has been shown to be able to propose a relatively balanced combination ratio for all reacting processes (please see Chen et al [13]), as stated in previous sections, not all experimental procedures will adopt the MLII to analyze the combinations of catalysts at the beginning. On the other hand, although all the participating elements have their own characteristics during the operational processes, they may produce mutual excitation, repulsion, or other interactive effects between each other, which will have a relative impact on the processes and results of entire operational processes.…”
Section: Discussion and Applicationmentioning
confidence: 99%
See 4 more Smart Citations
“…In the past, combinations were always estimated by empirical rule judgments, literature comparison simulations, circular errata corrections and so on. Although the MLII has been shown to be able to propose a relatively balanced combination ratio for all reacting processes (please see Chen et al [13]), as stated in previous sections, not all experimental procedures will adopt the MLII to analyze the combinations of catalysts at the beginning. On the other hand, although all the participating elements have their own characteristics during the operational processes, they may produce mutual excitation, repulsion, or other interactive effects between each other, which will have a relative impact on the processes and results of entire operational processes.…”
Section: Discussion and Applicationmentioning
confidence: 99%
“…By applying the notion of multi-choice circumstance, a toxicity-reacting environment with lofty consistences of mitigating catalysts and heavy metal pollutants can be generalized as (F, b, C). Based on the works of Chen et al [13], it is shown that the MLII could be a stable and sustainable mechanism for generating the most efficient combinations for reacting levels among all elements.…”
Section: Discussion and Applicationmentioning
confidence: 99%
See 3 more Smart Citations